Efficacy of XP-Endo Finisher and Passive Ultrasonic Irrigation on Modified Triple Antibiotic Paste Removal - Baran Can Sağlam (Cumhuriyet Dental Journal, 2019)
Objectives: The aim of this study was to compare conventional needle irrigation (CNI), passive ultrasonic irrigation (PUI), and XP-endo Finisher (XPF) techniques in terms of modified triple antibiotic paste (mTAP) removal.Materials and Methods: A total of 30 mandibular premolars were instrumented to a size F3 file. A mixture of mTAP was prepared by mixing 3 antibiotics, including 250 mg ciprofloxacin, 250 mg metronidazole, and 150 mg clindamycin, with 1 ml distilled water and applied into the root canals. The teeth were allocated into 3 equal groups, irrigation/agitation was performed and teeth were divided into two halves. The removal of mTAP was evaluated with a scanning electron microscope by using the 4 grade scoring system.Results: In the apical thirds, significant difference was found between PUI and CNI groups (p<0.05), whilst no significant difference was found among the other irrigation activation regimens (p> 0.05). No statistically significant difference was found between all groups in the middle third. In the coronal thirds, XPF removed significantly more mTAP than the CNI group (p<0.05). However, no difference was recorded among other groups (p>0.05). Conclusions: Passive ultrasonic irrigation and XPF file agitation demonstrated superior efficacy in removing mTAP from root canals compared to CNI.